Performance Evaluation Using Laser Doppler Vibrometer Sensing Technique on Advanced Lead Magnesium Niobate-lead Titanate Piezoelectric-material-based Microactuator for Hard Drive Head - Parinya Wattananukulchai; Don Isarakorn (My University, 2018)
This paper presents a microactuator for a dual-stage actuator (DSA) of hard disk drive (HDD) based on a lead magnesium niobate-lead titanate (PMN-PT) piezoelectric material and a comparative evaluation of its performance versus that of a traditional lead zirconate titanate (PZT) microactuator using the laser Doppler vibrometer (LDV) sensing technique.PZT microactuator technology has commonly been implemented in the read/write (R/W) magnetic head of HDD.It has a significant function, that is, it moves the magnetic head rapidly and accurately.In order to achieve both accurate positioning control on data tracks and high-speed access across another data track, advanced high-performance actuators and servo control technologies are necessary.An actuator with a wide stroke travel range is essential for HDD as it gives a high-speed access performance.In this study, we focused on comparing the proposed dual-stage PMN-PT head-based actuator with the existing PZT actuator that were mounted on a commercial head gimbal assembly (HGA) using an LDV to determine whether the proposed device could be a worthy replacement of the traditional PZT microactuator.Our experimental results show that the proposed PMN-PT microactuator provided more than twofold improvement in the stroke travel of the R/W magnetic head.Moreover, its dynamic behavior was suitable for assembling a high-density HDD in the future for big data storage without any needs to redesign the HGA nor to costly invest in new assembling machines in a production line.The comparative data of dynamic and static behaviors of PMN-PT versus PZT obtained in this study may be put to good use by sensor designers.Moreover, for many cyber-physical system designers, our data may make them take interest in PMN-PT as a better-performing sensor and an actuator for their systems.
Keywords: Microactuator; Lead (geology); Lead titanate; Laser scanning vibrometry; Barium titanate; Advanced Measurement and Metrology Techniques